2012
DOI: 10.1007/s00264-011-1447-8
|View full text |Cite
|
Sign up to set email alerts
|

Hip joint development in children with type IIb developmental dysplasia

Abstract: Despite obtaining normal sonograms at the end of treatment, some children with type IIb dysplasia may demonstrate radiographic evidence of persistent hip dysplasia over a longer follow-up period. Our results suggest that these children should be monitored until skeletal maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…12,13 Despite newborn screening and early treatment approaches, as a rare event, DDH may be encountered in older children particularly in developing countries. 14,15 In such late unilateral or bilateral cases, conservative approach is not recommended, and direct surgical interventions are emphasized as a necessity. 16 In studies examining the demographic characteristics of DDH, female gender has been reported as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Despite newborn screening and early treatment approaches, as a rare event, DDH may be encountered in older children particularly in developing countries. 14,15 In such late unilateral or bilateral cases, conservative approach is not recommended, and direct surgical interventions are emphasized as a necessity. 16 In studies examining the demographic characteristics of DDH, female gender has been reported as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 0 angle difference may exert a major repercussion on borderline hips: type IIa-, IIa+ or IIb with alpha angle value close to 60 0 . This category of patients is the main cause for controversial literature data on the increased rate of over-diagnosis [6,12,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2 Patient's X-rays-upper row representing preoperative state and state after bloody reposition, lower row shows pre-operative state and after operative treatment using an anterior approach As part of the pre-operative state, all patients underwent clinical examination, hip ultrasound and radiographic diagnostic and none of the patients underwent artrography during preparation state for the surgery [12,13]. The data analysis includes the state at the beginning of the treatment, the postoperative state, the state at discharge and control findings where we followed the development of the proximal femoral part up to 72 months on average.…”
Section: Methodsmentioning
confidence: 99%